1998
DOI: 10.1046/j.1365-2311.1998.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal patch use by foraging workers of Lasius fuliginosus, L. niger and Myrmica ruginodis

Abstract: 1. The predictions of the marginal value theorem, that foragers should spend more time in both better quality patches and more distant patches, were tested with three European ant species, Lasius fuliginosus, L. niger and Myrmica ruginodis. 2. As the quality of patches of sucrose solution increased, the feeding time of foraging workers of L. niger also increased. 3. At constant patch quality, feeding times of L. niger and M. ruginodis increased with increasing distance of the patch from the nest entrance. 4. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…A scout needs to drink up to its critical volume of food before returning to the nest. However, as expected from studies on the control of meal size in non-social insects (Bernays and Simpson, 1982;Simpson and Raubenheimer, 1995), other work in ants has shown that this critical volume is influenced by the concentration of sugar solution (Bonser et al, 1998;Josens et al, 1998), viscosity (Josens et al, 1998), distance (Bonser et al, 1998) of the food from the nest, and starvation level (Josens and Roces, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…A scout needs to drink up to its critical volume of food before returning to the nest. However, as expected from studies on the control of meal size in non-social insects (Bernays and Simpson, 1982;Simpson and Raubenheimer, 1995), other work in ants has shown that this critical volume is influenced by the concentration of sugar solution (Bonser et al, 1998;Josens et al, 1998), viscosity (Josens et al, 1998), distance (Bonser et al, 1998) of the food from the nest, and starvation level (Josens and Roces, 2000).…”
Section: Introductionmentioning
confidence: 71%
“…Ants in return defend the aphids from natural enemies. In general, the intensity of ant-aphid mutualism is positively correlated with honeydew quantity and quality as well as the sugar demand of the ants (Bristow, 1984;Bonser et al, 1998;. Honeydew is an aqueous solution consisting mainly of various sugars and amino acids (Auclair, 1963;Maurizio, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These social insects adjust their individual and collective response to these liquid food sources which differ in their chemical composition (Sudd & Sudd 1985;Breed et al 1987Breed et al , 1996ade Biseau et al 1992;Beckers et al 1993;de Biseau & Pasteels 1994;Bonser et al 1998;Völkl et al 1999) or their spatial distribution (Addicott 1979;Breed et al 1987;Itioka & Tamiji 1996).…”
Section: Introductionmentioning
confidence: 99%